Global Economic Policy Uncertainty and Sectoral Stock Resilience in Indonesia (Universitas Muhammadiyah Surakarta, 2025)
This study investigates the impact of Global Economic Policy Uncertainty (GEPU) on sectoral stock indices in Indonesia, specifically the financial, energy, and consumer cyclical sectors within the framework of the Arbitrage Pricing Theory (APT). Using monthly data from January 2021 to June 2025 and applying the Autoregressive Distributed Lag (ARDL) model, the research examines both the short- and long-run relationships between GEPU, key macroeconomic variables, and sectoral stock performance. The findings reveal that GEPU exerts a negative and significant influence on the financial and energy sectors, indicating capital withdrawal and higher risk premiums during periods of global uncertainty. In contrast, the consumer cyclical sector shows a positive response, suggesting short-term resilience as domestic consumption rebounded in the post-pandemic recovery phase. These results highlight that each sector responds differently to external shocks through distinct transmission channels: financial intermediation, commodity pricing, and consumer sentiment. The evidence provides valuable insights for both investors and policymakers to identify resilient sectors and to design strategic responses that enhance market stability and support sustainable economic growth (SDG 8) in periods of heightened global uncertainty.